Effective Organochlorine Pesticides Removal from Aqueous Systems by Magnetic Nanospheres Coated with Polystyrene - Lan, Jing; Cheng, Yang; Zhao, Zongshan (Journal of Wuhan University of Technology. Materials science edition, 2014)
In this paper, magnetic nanospheres coated with polystyrene （Fe3O4@PS） were prepared for the removal of organochlorine pesticides from aqueous solutions. The obtained Fe3O4@PS was round shape with diameter of 55±11 nm. The VSM results illustrated that its higher saturated magnetization was 36.76 emu g^-1 and it could be easily separated from aqueous solutions with a permanent magnet. The adsorption results showed that pesticides could be effectively adsorbed and the adsorption equilibrium time was less than 20 mins. The pseudo-second-order model was suitable to describe the adsorption kinetics. Compared with the Freundlich adsorption model, the adsorption data fitted well with Langmuir model. The effect of salinity and humic acid was also studied and the results illustrated that they could be neglected under optimized conditions. The asobtained sorbent showed a good performance with more than 93.3% pesticides removal in treating actual water samples.